1999
DOI: 10.1002/(sici)1099-1166(199909)14:9<784::aid-gps16>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Burden in carers of dementia patients: higher levels in carers of younger sufferers

Abstract: A comparative study of the clinical characteristics of early onset dementia (onset before the age of 65) and late onset dementia sufferers was conducted. The level of carer burden among carers of both groups was measured. Carer burden was significantly higher among carers of younger sufferers, although there were no significant differences between the groups in terms of clinical features such as severity of dementia or behavioural disturbance. Higher carer burden showed an inverse relationship to patient's age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 17 publications
4
57
0
1
Order By: Relevance
“…Of the seven qualitative studies, only two (Keady and Nolan, 1999;Garbutt, 2006) report their analyses. Similarly, of the six mixed methodology studies, only Freyne et al (1999) comment on the statistical analysis, although they do not give information about how interviews were analyzed.…”
Section: General Methodological Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the seven qualitative studies, only two (Keady and Nolan, 1999;Garbutt, 2006) report their analyses. Similarly, of the six mixed methodology studies, only Freyne et al (1999) comment on the statistical analysis, although they do not give information about how interviews were analyzed.…”
Section: General Methodological Issuesmentioning
confidence: 99%
“…Other studies which have considered these have focused on age and diagnostic factors. Freyne et al (1999) and Arai et al (2007) both compared the clinical characteristics and carer outcomes between younger and older people with dementia in a community sample. Both found that, despite no significant differences in cognitive functioning or behavioral disturbance, there was a significant difference between carers.…”
Section: Impact On the Family G E N E R A L C A R E R O U T C O M E Smentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that caregivers of younger people with dementia have higher levels of burden than their older counterparts, even when matched for severity of dementia and behavioral disturbance. 42 Support groups have a constructive role to play in offering people the opportunity to acknowledge their diagnosis and its consequences alongside peers in a similar position who understand their predicament. Support groups provide a space in which to share one's story, among listeners who understand and empathize, and, therefore, provide a setting in which acceptance of a diagnosis and the requisite adaptations is facilitated.…”
Section: Support Groupsmentioning
confidence: 99%
“…I tillegg til omsorgen for den demensrammede vil mange ektefeller få eneansvaret for barn og ungdom i familien. De har av den grunn en større psykisk belastning enn pårø-rende til eldre (45).…”
Section: Behandling Forløp Og Prognoseunclassified